METHODOLOGY OF FULL-WAVE SEISMIC FIELD MODELING WITHIN THE UKRAINIAN PART OF BLACK SEA SHELF (KERCH OFFSHORE AREA) - Tsybulskyi, V.; Kuzmenko, P.; Tyshchenko, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A full-wave modeling method on the ground of acoustic and elastic equations has been worked out for the part of Black sea shelf. Much attention has been given to influence of lower maikop deposits on features of seismic wave field. New results have been obtained for further analysis with purpose to gain effectiveness of using geological-geophysical data.